2001
DOI: 10.1074/jbc.m011527200
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage of a C-terminal Peptide Is Essential for Heptamerization of Clostridium perfringens ε-Toxin in the Synaptosomal Membrane

Abstract: Activation of Clostridium perfringens ⑀-protoxin by tryptic digestion is accompanied by removal of the 13 N-terminal and 22 C-terminal amino acid residues. In this study, we examined the toxicity of four constructs: an ⑀-protoxin derivative (PD), in which a factor Xa cleavage site was generated at the C-terminal trypsin-sensitive site; PD without the 13 N-terminal residues (⌬N-PD); PD without the 23 C-terminal residues (⌬C-PD); and PD without either the N-or C-terminal residues (⌬NC-PD). A mouse lethality test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
146
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(150 citation statements)
references
References 25 publications
(8 reference statements)
3
146
0
1
Order By: Relevance
“…It has been suggested that is a pore-forming toxin based on the following observations: (i) ε-toxin can form a large complex in the membrane of Madin-Darby canine kidney cells, and permeabilizes them (Petit et al 1997;Nagahama, Ochi, Sakurai, 1998); (ii) the large complex formed by ε-toxin is not dissociated by SDS-treatment, which is a common feature of pore-forming toxins (Petit et al 1997); and (iii) the CD spectrum of ε-toxin shows that it mainly consists of β-sheets (Habeeb, Lee, Atassi, 1973), as observed for pore-forming β-barrel toxins. A characteristic feature of ε-toxin is its potent neurotoxicity, which is not observed for other structurally well-defined pore-forming toxins (Miyata et al, 2001). Another characteristic of ε-toxin is the activation of the inactive precursor (ε-protoxin) by proteases such as trypsin, chymotrypsin (Hunter et al, 1992), and λ-protease produced by C. perfringens.…”
Section: Epsilon-toxin (ε ε ε ε ε)mentioning
confidence: 99%
“…It has been suggested that is a pore-forming toxin based on the following observations: (i) ε-toxin can form a large complex in the membrane of Madin-Darby canine kidney cells, and permeabilizes them (Petit et al 1997;Nagahama, Ochi, Sakurai, 1998); (ii) the large complex formed by ε-toxin is not dissociated by SDS-treatment, which is a common feature of pore-forming toxins (Petit et al 1997); and (iii) the CD spectrum of ε-toxin shows that it mainly consists of β-sheets (Habeeb, Lee, Atassi, 1973), as observed for pore-forming β-barrel toxins. A characteristic feature of ε-toxin is its potent neurotoxicity, which is not observed for other structurally well-defined pore-forming toxins (Miyata et al, 2001). Another characteristic of ε-toxin is the activation of the inactive precursor (ε-protoxin) by proteases such as trypsin, chymotrypsin (Hunter et al, 1992), and λ-protease produced by C. perfringens.…”
Section: Epsilon-toxin (ε ε ε ε ε)mentioning
confidence: 99%
“…, that encodes ProET (20) was digested with EcoRI and XhoI to abolish the HindIII site in the non-coding region, blunt-ended, and then religated. Two synthetic oligonucleotides, 5Ј-TATGGGCCATCATCATCATCATC-ACAGCAGCGGCATCGAAGGTCGTATGAGACGTGCGTCTGTTAA-3Ј (sense; the His 6 tag, factor Xa, and protein kinase A recognition sequences are underlined, doubly underlined, and italicized, respectively) and 5Ј-AGCTTTAACAGACGCACGTCTCATACGACCTTCGATGCCG-CTGCTGTGATGATGATGATGATGGCCCA-3Ј (antisense), were annealed and cloned into the above plasmid, which had been digested with NdeI and HindIII.…”
Section: Construction Of Recombinant Proet and Et-a Plasmid Pep1mentioning
confidence: 99%
“…This toxin accumulates mainly in the brain and kidneys when intravenously injected into rats (14), causing injury to neuronal cells (15)(16)(17) and cerebral blood vessels (18). One characteristic feature of the toxin is its extraordinarily high potency; 20 ng of ET kills a mouse within 1 h. 2 We have previously shown that proteolytic activation of ⑀-protoxin (ProET) is due to the removal of a C-terminal peptide (19,20) and that activated ET forms a heptamer in rat synaptosomal membranes (20). Similar ET oligomerization has been reported for Madin-Darby canine kidney (MDCK) cell membranes, where the potassium ion permeability is increased by the toxin (21).…”
mentioning
confidence: 99%
“…A prototoxina épsilon utilizada como antígeno no ELISA Indireto, cedida pelo Laboratório de Enfermidades Infecciosas dos Animais da Faculdade de Medicina Veterinária de Araçatuba, UNESP Araçatuba, SP, produzida in house (Veschi 2006) teve sua toxigenicidade avaliada pela observação de sintomatologia de camundongos Balb-c (peso médio 17-20g) inoculados via endovenosa com diferentes diluições da prototoxina ativada com tripsina 0,05% (Miyata et al 2001), por eletroforese em gel de poliacrilamida 12 % (SDS--PAGE) para caracterização da fração protéica (Asubel et al 1994) e pela neutralização com antitoxina homóloga.…”
Section: Detecção E Quantiϐicação De Anticorpos Antitoxina éPsilonunclassified